Power Quality Evaluation of a Photovoltaic System on an Electric Grid - Nascimento, Mauro (2016)
This paper focuses on tests of photovoltaic systems in order to address two case studies with silicon monocrystalline and silicon polycrystalline panels, respectively. The first case is an identification of the three parameters of the single-diode equivalent circuit for modelling photovoltaic systems with conclusion about the inevitably age degradation. A comparison between experimental observed and computed I-V and V-P characteristics curves is carried out at standard test conditions. The second case is an experimental observation on a photovoltaic system connected to an electric grid in what regards the quality of the energy injected into the grid. A measuring of the harmonic content in the voltage and in the current waveforms at the terminals of the photovoltaic system is carried out in order to conclude about the conformity with the Standard EN 50160 and the IEEE 519-1992, respectively.